Reorganisation of a legal entity: the essence and understanding of its manifestation (creation or termination) - T. S. Stupak (Bulletin of Kharkiv National University of Internal Affairs)
The problematic issues related to the legislator’s priority task of regulating changes in the property status of a legal entity in the course of its reorganisation are outlined, which ensures the organisational and legal transformation of the organisation through effective redistribution of resources and enhancing the modernisation of the country’s economic stability as a whole.